Fungicides evaluation to control of panicle blast in irrigated rice - Scheuermann, Klaus Konrad; Eberhardt, Domingos Sávio (Revista de Ciências Agroveterinárias, 2011)
Chemical control of panicle blast, caused by Pyricularia oryzae, is ineffective in many cases, due to the use of non-recommended products or applied improperly. In order to evaluate fungicides efficiency in the control of panicle blast, two experiments were performed in Itajaí and Garuva counties of Santa Catarina state, during 2008/09 planting season. The fungicides were evaluated as single application, at R3 stage (early heading) and two applications at R2 (late boot) and R4 stage (full heading), in an outflow of 200 L ha-1. It was found that when the incidence of panicle blast (PB) was 37.5%, there was a higher level of disease control in treatments with two applications of fungicides, compared to treatments receiving only one application. On the other hand, when the incidence of PB was 20.6%, no significant differences between treatments with one or two applications of fungicides were verified. Two applications of propiconazol + trifloxystrobin, tebuconazol + trifloxystrobin, the tank mixture tricyclazol + tebuconazol and the tricyclazol followed by tebuconazol + trifloxystrobin, proved to be over 90% effective to control panicle blast. It's not observed significant gains in productivity resulting from the use of fungicides.